THE REALIZATION OF REQUESTIVE SPEECH ACTS IN SUNDANESE - Iceu Kusmawati, - (2008)
This paper entitled "The Realization of Requestive Speech Acts in Sundanese (A Case Study at SMUN 2 Kuningan)" is aimed at finding the most common patterns or strategies of requestive speech acts in Sundanese by identifying the social variables and politeness implications of such patterns. This study employed qualitative research design. The respondents of this research were 18 males and 12 females of the second grade students of a Senior High School in Kuningan. The data were collected through Discourse Completion Tests (DCTs) and analyzed by using Blum-Kulka's (1989) framework. This research found that the respondents manifested the requests in various strategies, i.e. mood derivable, explicit performatives, hedged performatives, locution derivable, want statement, suggestory formula, preparatory, strong hints, and mild hints. The study reveals that the most commonly used request strategy is preparatory, viewed from the nature of preparatory strategy as polite strategy, which means that most respondents use polite utterances. In addition, the result of common patterns shows that social variables such as: power, social distance and ranking of imposition play a role in the realizations of requestive strategy by the respondents. For example, when gender is a function, this study found that males and females manifest different strategies when requesting. As an alternative strategy, males used mood derivable strategy frequently than females, where it was informal-setting, high-relative power and close-social distance conditions. Females preferred using want statement to mood derivable. Finally, this study concludes that preparatory is the most appropriate requestive strategy that is also considered as the polite strategy. The use of this strategy is related to politeness and social variables, the higher requestee's social position, the more polite the requester in making a request.